QUALITY OF PLYWOODS OBTAINED FROM Melia azedarach COMBINED WITH Pinus taeda, PRODUCED WITH UREA-FORMALDEHYDE AND PHENOL-FORMALDEHYDE RESINS - Iwakiri, Setsuo; Trianoski, Rosilani; Castro, Vinicius Gomes; Parchen, Carlos Frederico Alice; Araújo, Roberto Daniel (Floresta, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Abstract This study was developed to evaluate the quality of plywood produced from Melia azedarach in combination with Pinus taeda, glued with urea-formaldehyde resin (UF) and phenol formaldehyde (PF). Panels were produced using five veneers of Melia azedarach only, five veneers of Pinus taeda and also with faces made of Melia azedarach and core with Pinus taeda. The panels were evaluated by glue line shear tests and by static bending in parallel and perpendicular directions. The higher contents of extractives in Melia azedarach wood did not reduce the glue line shear strength between the layers. For both UF and PF glues, panels produced with veneers of Melia azedarach showed better results on static bending and glue line shear tests. The results indicate great potential of Melia azedarach wood in plywood production, both for internal use (UF), and for external use (PF). Keywords: Cinamomo; wood veneer; glue line. Resumo Qualidade de painéis compensados de Melia azedarach em combinação com Pinus taeda produzidos com resina uréia-formaldeído e fenol-formaldeído. O objetivo deste trabalho foi avaliar a qualidade de painéis compensados de Melia azedarach em combinação com Pinus taeda, produzidos com resina ureia-formaldeído (UF) e fenol-formaldeído (FF). Foram produzidos painéis com todas as cinco lâminas de Melia azedarach e de Pinus taeda, e capas de Melia azedarach e miolo de Pinus taeda. Os painéis foram avaliados por meio de ensaios de cisalhamento da linha de cola e flexão estática paralela e perpendicular. Maiores teores de extrativos presentes na madeira de Melia azedarach não prejudicaram a resistência da linha de cola entre as lâminas. Tanto para a colagem uréica, quanto para a fenólica, os painéis produzidos com lâminas de Melia azedarach apresentaram melhores resultados nos ensaios de flexão estática e de cisalhamento da linha de cola. Os resultados obtidos indicam grande potencial da madeira de Melia azedarach para produção de painéis compensados, tanto para uso interior (UF), quanto para uso exterior (FF). Palavras-chave: Cinamomo; lâminas de madeira; linha de cola. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>